ANALISIS DALALAH BAHASA ARAB ASPEK LISAN DAN TERTULIS - Sari Uswatun Hasanah (STAI Darul Quran Payakumbuh, 2016)
Dalalah is a branch of science in Arabic which studies about meaning. It is very often used in daily spoken language concerning kinds of meaning, word choice, and connotation. In written language, the structure of sentences, and quotation marks include the content of dalalah. There are some fields relating to philology, communication, and semiotics. Those fields also study meaning at the level of words, phrases, sentences, and texts. The scope of the research is on the meaning of signs, relationships among different linguistic units (ةيللادلا تاقلعلا) like homonym, synonym, and antonym. Some linguists state that the words having one meaning is called synonym رتلافدا. Then, a word which has several meanings is called homonym ىظفللا كرتشملا, and the words which have contrastive meaning are called antonym دادضلأا. The writer finds many miscomprehension between speakers and listeners. For example, when an ustad or speaker delivers a speech at the front of his audience, not all of the information and message told in the speech understanadle for his listeners. It is caused by word choice, phrases, and sentences they are not so suitable to the listeners. The purpose of the research is to discuss and analyze the meaning of words in spoken and written languages. Then, another aim is at minimizing the mistakes of using vocabulary, phrases, structure, and the context of sentences both in spoken and written languages.